2000
DOI: 10.1182/blood.v95.12.3878.012k26_3878_3884
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland mucosa-associated lymphoid tissue lymphoma immunoglobulin VH genes show frequent use of V1-69 with distinctive CDR3 features

Abstract: Salivary gland mucosa associated lymphoid tissue (MALT) type lymphomas are B-cell neoplasms that develop out of a reactive infiltrate, often associated with Sjögren's syndrome. Previous reports from our laboratory involving 10 patients suggested these lymphomas expressed a restricted immunoglobulin (Ig)VH gene repertoire with over use ofV1-69 gene segments. To better determine the frequency ofV1-69 use and whether there may also be selection for CDR3 structures, we sequenced the VH genes from 15 additional ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
38
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 38 publications
5
38
0
Order By: Relevance
“…The presence of somatic mutations and intraclonal diversity indicates that these cells were stimulated to proliferation under conditions in which T cell-derived signals re-quired for mutation were present. The overall number of common mutations detected at the different time points (4-8 mutations, 1.8-3.5%) was not high, similar to the levels observed in nonmalignant IgMϩ/IgDϪ peripheral blood lymphocytes, in SS-associated MESA as well as in salivary gland MALT lymphomas (7,8).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The presence of somatic mutations and intraclonal diversity indicates that these cells were stimulated to proliferation under conditions in which T cell-derived signals re-quired for mutation were present. The overall number of common mutations detected at the different time points (4-8 mutations, 1.8-3.5%) was not high, similar to the levels observed in nonmalignant IgMϩ/IgDϪ peripheral blood lymphocytes, in SS-associated MESA as well as in salivary gland MALT lymphomas (7,8).…”
Section: Discussionsupporting
confidence: 67%
“…The meaning of such a feature has been debated. In fact, a low R/S ratio in CDRs in MESA and in some MALT lymphomas was reported in previous studies (7,8). It has been suggested that the residues in the CDRs are conserved to maintain the binding to antigens that are important for B cell stimulation and survival.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The G6 CRI may also be useful for monitoring B cells and Abs that bind to and neutralize HCV and MERS-CoV, respectively (Chan et al, 2001;Tang et al, 2014;Ying et al, 2015). In the emerging field of oncoimmunology, the high presence of G6 CRI on unmutated BCRs seen in IGVH1-69-encoded B-CLL (Chang et al, 2016;Hamblin et al, 1999), and the recognition of other IGHV1-69 disorders involving pathophysiologic B cell expansions (Chan et al, 2001;Miklos et al, 2000) could provide an avenue of therapeutic intervention through hG6.3-mediated immune clearance. In addition, hG6.3-based idiotype mapping (Idio-Seq) could add an important new dimension to the field of immune recognition where advances in the high-throughput sequencing and analysis of expressed Ab repertoires (BCR-seq) in peripheral blood B cells and LC-MS/MS proteomic spectrotyping of antigen-specific Abs (IG-seq) allow us to characterize, with unparalleled accuracy, the serological repertoire to each of the Ab components (Lee et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, the anti-Id + G6 51p1 alleles are overwhelmingly predominant in this disease (Johnson et al, 1997;Keating et al, 2003). Several other biased F-allelic IGHV1-69 Ab responses and associations with disease processes have been reported (Chan et al, 2001;Miklos et al, 2000;Steininger et al, 2012;Tang et al, 2014;Yeung et al, 2016;Ying et al, 2015). In influenza infection, the biased use of IGHV1-69 F-alleles in the production and serum titers of broadly neutralizing antibodies to the influenza A hemagglutinin (HA) stem domain (HV1-69-sBnAbs) occurs Pappas et al, 2014).…”
Section: Introductionmentioning
confidence: 89%